Program Pelatihan Pemasangan Instalasi Listrik Gedung dan Daya bagi Pemuda Kopelma Darussalam - Lubis, Rakhmad Syafutra; Siregar, Ramdhan Halid; Walidainy, Hubbul; Syukri, Mahdi; Jalil, Saifuddin Muhammad (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
The Training Program on Building Electrical and Power Installation for Kopelma Darussalam Youth is designed to enhance the technical skills of the younger generation in the electrical field. This program aims to equip participants with both theoretical knowledge and practical experience related to the installation of electrical systems in buildings, including lighting systems and power distribution networks. The training covers topics such as the introduction to electrical components, installation planning, installation techniques, safety standards, and troubleshooting electrical systems.The primary target of this program is local youth with potential to develop technical competence in the electrical sector, enabling them to compete in the workforce or establish independent businesses. By employing a project-based approach, participants are expected to apply their skills professionally and in compliance with industry standards. Furthermore, this program contributes to empowering youth as valuable community assets to support sustainable local development.